2015
DOI: 10.1038/srep11010
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetic refrigeration properties in Mn-rich Ni-Mn-Sn ribbons by optimal annealing

Abstract: The influence of annealing time on temperature range of martensitic phase transition (ΔTA-M), thermal hysteresis (ΔThys), magnetic hysteresis loss (ΔMhys), magnetic entropy change (ΔSM) and relative refrigeration capacity (RC) of the Mn-rich Ni43Mn46Sn11 melt spun ribbons have been systematically studied. By optimal annealing, an extremely large ΔSM of 43.2 J.kg−1K−1 and a maximum RC of 221.0 J.kg−1 could be obtained respectively in a field change of 5 T. Both ΔTA-M and ΔThys decreases after annealing, while Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…31 Under 50 kOe, the DS m of the present Ni-Mn-Ga-Cu microwire (À8.3 J/kg K) is lower than the other alloys, but the FWHM of the Ni-MnGa-Cu microwires ($13 K) is larger than those of other NiMn-based ribbons (R) or bulk (B) alloys (0.9-6.5 K). 3,9,14,17,19,40,41 The obtained RC in Ni-Mn-Ga-Cu microwire (78.0 J/kg) is comparable with those of Ni-Mnbased alloys (70-115 J/kg) 3,9,40 and superior to those of NiMn-Ga-Cu bulk alloys (72-75 J/kg). 14,17,19 On the other hand, when compared to Gd 42 or LaFe 13Àx Si x 43 alloys, the Ni-Mn-Ga-Cu microwires are rare-earth free and thus cost effective, which helps for the practical applications.…”
supporting
confidence: 49%
“…31 Under 50 kOe, the DS m of the present Ni-Mn-Ga-Cu microwire (À8.3 J/kg K) is lower than the other alloys, but the FWHM of the Ni-MnGa-Cu microwires ($13 K) is larger than those of other NiMn-based ribbons (R) or bulk (B) alloys (0.9-6.5 K). 3,9,14,17,19,40,41 The obtained RC in Ni-Mn-Ga-Cu microwire (78.0 J/kg) is comparable with those of Ni-Mnbased alloys (70-115 J/kg) 3,9,40 and superior to those of NiMn-Ga-Cu bulk alloys (72-75 J/kg). 14,17,19 On the other hand, when compared to Gd 42 or LaFe 13Àx Si x 43 alloys, the Ni-Mn-Ga-Cu microwires are rare-earth free and thus cost effective, which helps for the practical applications.…”
supporting
confidence: 49%
“…The as-cast samples were wrapped by tantalum foil and annealed in a high-vacuum quartz tube at 1173 K for 96 h, followed by quenching in ice water. It is noted that the effect of different heat treatments on the magnetic and magnetocaloric properties has been studied intensively in NiMn-based Heusler alloys [22][23][24][25]. It is revealed that the MCE can be largely improved by optimizing the heat treatment, e.g., an optimized annealing method can reproduce the excellent functional properties of Ni-Co-Mn-Al films in ribbons [25].…”
Section: Methodsmentioning
confidence: 99%
“…The rapid solidification based on melt-spinning technique has been proven to be an effective processing route for the preparation of ribbon shaped ferromagnetic shape memory alloys [40,41,42,43,44,45,46,47,48,49,50]. This method can avoid long time post heat treatment to achieve the composition homogeneity.…”
Section: Resultsmentioning
confidence: 99%